O papel do BIRD e BID nas reformas educacionais no Brasil e no Paraguai na década de 1990 - Duarte, Luiza Franco (2016)
Throughout the 1990s, several Latin American countries underwent deep economic-political reforms linked to loans and financing from the World Bank Group for the dissemination of the Neoliberal Project. In March 1990, the World Conference on Education for All (UNESCO, 1990) expresses the convergence of the function and conception of school education along the lines defined by the Washington Consensus, 1989. It marks a historic moment of rooting of the form of organization and management of the education before the process of economic, political, social and cultural restructuring, in construction with the accomplishment of the Reformation of the Latin American States, keeping the proportions as the peculiarities of each country and also of the level of effectiveness of the prescription of the Washington Consensus, put into practice. In this way, the present bibliographic and documentary research sought to present the realities and conjunctures of Brazil and Paraguay through the educational legislation produced in the 1990s, based on BIRD and BID recommendations to support the process of penetration of the neoliberal project in these countries. The BIRD or BID loans for school education had their objectives directed to the political orientations of the governments for the maintenance of the economic order and the deepening of the internationalization and concentration of capital for the financial sector. Due to the large financial disbursements of these organizations, with the demand for guarantees from counterparts of countries and / or federated borrowers, there was a significant increase in external debts, in the form of legal-political organization of the states, and in the ideological spread of neoliberalism, which were presented in the said loans for projects in various sectors of the economy and the social area, particularly those for school education. This research generally involves an understanding of the role of Multilateral International Organizations in the formulation and implementation of educational policies guided by the Neoliberal Project; specifically, the identification in the Brazilian and Paraguayan context of the influence of IBRD and IDB through technical and financial advice. It is necessary to emphasize that the loans of these Financial Agencies for the mentioned countries was not limited to the technical advice, but mainly it permeated an ideological and political character of the capitalism in its new model of expression. The implications of these agreements were on the organizational mode and the direction of educational policies. It did not have an eminently economic character, but it covered the social, political and ideological aspects. Therefore, the characteristics of the neoliberal reforms in Latin America, in terms of educational policies, highlighting Brazil and Paraguay were the expansion of schooling time, through the stipulation of obligatory years, establishes a minimum of workload and school days through of a school calendar. Another aspect is the redistribution of functions and responsibility between the levels of the systems, besides the specializations and rationalization of human resources.